2007
DOI: 10.1007/s11146-007-9083-1
|View full text |Cite
|
Sign up to set email alerts
|

Do Repeated Wildfires Change Homebuyers’ Demand for Homes in High-Risk Areas? A Hedonic Analysis of the Short and Long-Term Effects of Repeated Wildfires on House Prices in Southern California

Abstract: Hedonic property method, Forest fires, Implicit prices, Willingness to pay,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 14 publications
1
39
0
2
Order By: Relevance
“…Our data are limited to one wildfire and post‐wildfire flooding event. Studies estimating the impact of multiple events remain less common (Mueller et al, ) and are an area of further research. Coconino County and its partners spent over $30 million following the Schultz Fire to protect communities from future flood danger (Coconino, County, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are limited to one wildfire and post‐wildfire flooding event. Studies estimating the impact of multiple events remain less common (Mueller et al, ) and are an area of further research. Coconino County and its partners spent over $30 million following the Schultz Fire to protect communities from future flood danger (Coconino, County, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, those non-water related facilities end up with statistically insignificant results. These may suggest that there is no use for adding those none water-related recreation activities or facilities such as kid playground and fun fair to the coastal parks because they may play a role in detract not adds to the visitors' satisfaction (Loomis & Richard, 1997;Mueller et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Individual tolerance for fire risk can impact land use change. Economic studies [24,25] of land use change have shown that some risk averse landowners are less likely to develop fire prone areas, although this aversion is often balanced by the fact that many fire prone areas also have natural amenities that are desired by home owners (for instance fire prone steep slopes may also offer wonderful views) [26,27]. While it is a common assumption in many fire prone areas that landowners typically rebuild after a fire, empirical evidence suggest that this is not always the case, and indeed a re-wilding of some previously subdivided land may take place after fires [28].…”
Section: Fire Risk and The Management Of Fire Risk As Drivers Of Landmentioning
confidence: 99%
“…In some municipalities local zoning has made these areas out of bounds for development, while in others it may be more difficult for developers to insure homes built in VSFH zones. While this policy has been criticized as not being strong enough to deter land use change [24,31], the intention of the regulation was to do just that.…”
Section: Fire Risk and The Management Of Fire Risk As Drivers Of Landmentioning
confidence: 99%